LINC00707 contributes to hepatocellular carcinoma progression via sponging miR‐206 to increase CDK14. Issue 7 (29th November 2018) - Tu, Jianfei; Zhao, Zhongwei; Xu, Min; Chen, Minjiang; Weng, Qiaoyou; Wang, Jiangmei; Ji, Jiansong
Abstract: Recently, increasing numbers of long noncoding RNAs (lncRNAs) have been found to be aberrantly expressed in various cancers. However, the roles of lncRNAs in hepatocellular carcinoma (HCC) progression is largely unknown. In our current study, we identified that long intergenic nonprotein‐coding RNA 707 (LINC00707) was remarkably elevated in HCC cells, indicating that LINC00707 was involved in HCC development. Subsequently, LINC00707 was significantly decreased in HepG2 and Huh7 cells. The in vitro functional assays demonstrated that knockdown of LINC00707 significantly reduced HCC cell proliferation, induced cell apoptosis, and blocked the cell cycle progression. In addition, HCC cell migration and invasion was also greatly inhibited by downregulation of LINC00707. Increasing evidence has indicated that lncRNAs can act as molecular sponges of microRNAs. Currently, we observed that microRNA‐206 (miR‐206) was dramatically inhibited in HCC cells and LINC00707 can modulate HCC development through sponging miR‐206. The binding correlation between LINC00707 and miR‐206 was confirmed by dual‐luciferase reporter assay, RNA pull down and RNA immunoprecipitation assay in our study. Moreover, cyclin‐dependent kinase 14 (CDK14) was predicted as a target of miR‐206 and we found that miR‐206 suppressed CDK14 levels in HCC cells. Finally, in vivo assays were used and it was proved that silence of LINC00707 can restrain HCC development through modulating miR‐206 to upregulate CDK14. In conclusion, it was implied that LINC00707 can lead to HCC progression through sponging miR‐206 and modulating CDK14. Abstract : We observed that long intergenic nonprotein‐coding RNA 707 (LINC00707) was increased in hepatocellular carcinoma (HCC) cells and LINC00707 silence was able to greatly repress HCC progression, and the correlation between LINC00707 and mciroRNA‐206 (miR‐206) was validated in our research and downregulation of LINC00707 increased miR‐206 expression in HCC cells. Then, cyclin‐dependent kinase 14 (CDK14) was predicted as a target of miR‐206 and the correlation between them was proved in our study. In conclusion, our data implied that LINC00707/miR‐206/CDK14 axis participated in HCC development and LINC00707 might be a biomarker for HCC.